2011
DOI: 10.1371/journal.pone.0022581
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Activated Recombinant Factor VII in Liver Resection and Liver Transplantation: Systematic Review and Meta-Analysis

Abstract: Background and AimIntraoperative blood loss is a frequent complication of hepatic resection and orthotopic liver transplantation. Recombinant activated coagulation factor VII (rFVIIa) is a coagulation protein that induces hemostasis by directly activating factor X. There is no clear information about the prophylactic value of rFVIIa in hepatobiliary surgery, specifically in liver resection and orthotopic liver transplantation. The aim of this study was to assess the effect of rFVIIa prophylaxis to prevent mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 22 publications
(40 reference statements)
2
9
0
Order By: Relevance
“…Similar from the previous studies [26][27][28], our meta-analysis suggested that rFVIIa didn't increase mortality (RR=1.00, 95%CI=0.82-1.21, P=0.98) and total thromboembolic events (RR=1.13, 95%CI=0.94-1.36, P=0.20) compared with placebo group. Arterial events were significantly higher in rFVIIa group (RR=1.38, 95%CI=1.08-1.77, P=0.01).…”
Section: Discussionsupporting
confidence: 87%
“…Similar from the previous studies [26][27][28], our meta-analysis suggested that rFVIIa didn't increase mortality (RR=1.00, 95%CI=0.82-1.21, P=0.98) and total thromboembolic events (RR=1.13, 95%CI=0.94-1.36, P=0.20) compared with placebo group. Arterial events were significantly higher in rFVIIa group (RR=1.38, 95%CI=1.08-1.77, P=0.01).…”
Section: Discussionsupporting
confidence: 87%
“…Although initially promising, more recent randomized controlled trials have found no benefit in terms of perioperative transfusion requirements with rVFIIa . Similarly, the results of two systematic reviews and meta‐analyses as well as a Cochrane review have found no differences in mortality or transfusion requirements between patients receiving rFVIIa or placebo prior to liver transplantation. Lastly, enthusiasm for rVFIIa has waned since it is introduction in 2005 as prothrombin complex concentrates (PCC) with factor VII became available.…”
Section: Hemostatic Agentsmentioning
confidence: 99%
“…In patients with and without liver diseases, administration of rFVIIa shortened the abnormal PT value [119][120][121][122][123][124]. However, in randomized clinical trials rFVIIa administration to patients with cirrhosis proved ineffective in controlling bleeding from varices or bleeding during surgery [24,120,[125][126][127].…”
Section: Recombinant Activated Factor VIImentioning
confidence: 99%